Analysis of voltage drop regulation and control methods during the soft starting of asynchronous electric motors - Ikromjon U. Rakhmonov; Shukhrat I. Djuraev (PROBLEMS OF ENERGY AND SOURCES SAVING, 2026)
Relevance: The direct starting of asynchronous electric motors often leads to voltage drops, which negatively impact the energy efficiency and reliability of industrial power networks. Consequently, the implementation of soft starters is regarded as a highly relevant solution in modern practice. Aim: The study aims to develop theoretical and practical approaches to minimizing voltage drops during motor startup, enhancing power network stability, and extending the operational lifespan of electrical equipment. Methods: The research involves analyzing the challenges associated with starting asynchronous motors, substantiating the efficiency of soft starting technologies, and examining their integration with automated control systems. Results: Findings demonstrate that the use of soft starters reduces voltage drops, improves network stability and equipment reliability, ensures energy efficiency, and contributes to establishing a safe and sustainable energy system for industrial enterprises.